2021
DOI: 10.3389/fmicb.2021.711377
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversity of the Ostreid Herpesvirus Type 1 Across Time and Location and Among Host Species

Abstract: The mechanisms underlying virus emergence are rarely well understood, making the appearance of outbreaks largely unpredictable. This is particularly true for pathogens with low per-site mutation rates, such as DNA viruses, that do not exhibit a large amount of evolutionary change among genetic sequences sampled at different time points. However, whole-genome sequencing can reveal the accumulation of novel genetic variation between samples, promising to render most, if not all, microbial pathogens measurably ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 86 publications
(151 reference statements)
3
18
0
Order By: Relevance
“…Our findings also showed that OsHV-1 µVar populations are much more diverse than previously thought. This is congruent with results from Delmotte et al showing that OsHV-1 µVar from the Bay of Brest and Thau Lagoon constitute two distinct viral populations (Delmotte et al, 2020) as well as with the recent relatively high estimate of OsHV-1 evolutionary rate (Morga et al, 2021). We therefore argue it is now necessary to combine common approaches relying on the generation and the analysis of consensus genomes to intra host diversity characterization in order to accurately study the epidemiology of DNA viruses (Renner and Szpara, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Our findings also showed that OsHV-1 µVar populations are much more diverse than previously thought. This is congruent with results from Delmotte et al showing that OsHV-1 µVar from the Bay of Brest and Thau Lagoon constitute two distinct viral populations (Delmotte et al, 2020) as well as with the recent relatively high estimate of OsHV-1 evolutionary rate (Morga et al, 2021). We therefore argue it is now necessary to combine common approaches relying on the generation and the analysis of consensus genomes to intra host diversity characterization in order to accurately study the epidemiology of DNA viruses (Renner and Szpara, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…With the recent advances in genomic sequencing efforts, considerable genotypic variations within the OsHV-1 species have been established. These variations are associated with different host species as well as temporal and geographical factors ( 59 61 ), supporting the possible emergence of specific variants in New Zealand. The current results indicate that genomic sequence comparison of strains between New Zealand, Australia, Europe, and the United States may indeed be a fruitful area for future research.…”
Section: Discussionmentioning
confidence: 81%
“…With the recent advances in genomic sequencing efforts, considerable genotypic variations within the OsHV-1 species have been established. These variations are associated with different host species as well as temporal and geographical factors [89][90][91], supporting the possible emergence of speci c variants in NZ.…”
Section: A Distinct Oshv-1 Variant Speci C To New Zealandmentioning
confidence: 99%
“…With the recent advances in genomic sequencing efforts, considerable genotypic variations within the OsHV-1 species have been established. These variations are associated with different host species as well as temporal and geographical factors (59)(60)(61), supporting the possible emergence of specific variants in New Zealand. The current results indicate that genomic sequence comparison of strains between New Zealand, Australia, Europe, and the United States may indeed be a fruitful area for future research.…”
Section: Figmentioning
confidence: 80%